Workshop on Assistance in Curriculum Development “Merdeka Belajar Kampus Merdeka” at Nahdlatul Ulama University, West Kalimantan - Dona Fitriawan; Agung Hartoyo; Edy Yusmin; Ade Mirza; Nurfadilah Siregar; Revi Lestari Pasaribu (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This community service activity began with the collaboration between Tanjungpura University and Nahdhatul Ulama University in West Kalimantan, especially in terms of infrastructure, teaching staff (lecturers) and student management. In responding to the new policy from the Ministry of Education, Culture, Research, and Technology regarding the MBKM policy, a new curriculum development policy was made which was closely related to the ministry's policy. This form of service is a workshop or training on "Workshop for Assistance in the Development of the MBKM Curriculum at the Nahdlatul Ulama University, West Kalimantan". This workshop was attended by Lecturers, Education Personnel, and Students at UNU West Kalimantan as research subjects. The method for implementing this mentoring workshop includes: 1) drafting which will become an MBKM guide book, 2) making and delivering powerpoint materials delivered by resource persons, 3) mentoring workshops on curriculum development until it is finished. The activities are in the form of workshops. The product is in the form of a Guide Book which will serve as a guide for the University in implementing the Tri Dharma of Higher Education based on the MBKM curriculum. The technique of collecting data is by using observation, interview, and documentation techniques. In the data collection tools in the form of observation sheets, interviews, and documentation sheets. The Service Plan activities are: 1) Preparation: determining the location and obtaining the implementation permit in this workshop activity; 2) Implementation: conducting workshops, analyzing test results, and mentoring in MBKM curriculum development workshops, conducting workshops in class; 3) Final: The output of this publication will be a service publication article published in a national journal. The result of this service is the implementation of curriculum development workshops and the establishment of an MBKM Curriculum Guide and the establishment of visiting lectures with UNU West Kalimantan